2017
DOI: 10.1108/k-10-2016-0297
|View full text |Cite
|
Sign up to set email alerts
|

A study of correlation between investor sentiment and stock market based on Copula model

Abstract: Purpose This paper aims to capture tail dependence between sentiment index and Shanghai composite index (SCI) by proposing a sentiment index based on text mining. Design/methodology/approach Online text mining and the Copula model were used in this study. Findings First, the paper finds herding effect in the expression of investors’ sentiment from online text data, and the usage occurrence frequency of most vocabulary is less correlative with SCI. Second, given these two features, the paper uses weighted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Sariannidis et al (2016) examined the reaction of stock market in Europe due to change in weather condition and found that it has affected DJSI (Dow Jones Sustainability Indices) Europe positively. Sayim and Rahman (2015), Yao et al (2017) analyzed that investor sentiment index has a positive relation with the Turkish stock and Shanghai Composite Index, respectively. Sailaja and Mandal (2018) examined the effect of oil price, FIIs, dollar value on auto, IT, bank and energy indices of BSE from 2009 to 2015.…”
Section: Gold Price and Stock Market Movement In Various Countriesmentioning
confidence: 99%
“…Sariannidis et al (2016) examined the reaction of stock market in Europe due to change in weather condition and found that it has affected DJSI (Dow Jones Sustainability Indices) Europe positively. Sayim and Rahman (2015), Yao et al (2017) analyzed that investor sentiment index has a positive relation with the Turkish stock and Shanghai Composite Index, respectively. Sailaja and Mandal (2018) examined the effect of oil price, FIIs, dollar value on auto, IT, bank and energy indices of BSE from 2009 to 2015.…”
Section: Gold Price and Stock Market Movement In Various Countriesmentioning
confidence: 99%
“…Negative weights correspond to so called 'short sale'. In practice, financial data are often non-Gaussian distributed and the covariance analysis may fails to anticipate cross-correlated extreme events, appearing for many assets simultaneously [6,160]. This typically happens during the crisis, and as non-predicted by the Gaussian model is potentially dangerous for equity holders.…”
Section: Multivariate Gaussian Distributionmentioning
confidence: 99%
“…In a top-down approach, among of empirical evidence that concluded sentiment investor as a determinant in a stock market [18], [22], [33], [34], [35], [36](, [37], [38], [39], [40], [41] analyzed financial blogs and online news articles to develop a public mood dynamic prediction model for stock markets. The result assesses the emotional content of commentary on current stock or financial issues that can effectively forecast stock price movement [42].…”
Section: Introductionmentioning
confidence: 99%